1999
DOI: 10.1177/019262339902700505
|View full text |Cite
|
Sign up to set email alerts
|

Transponder-Induced Sarcoma in the Heterozygous p53+/- Mouse

Abstract: Heterozygous p53 +/-transgenic mice are being studied for utility as a short-term alternative model to the 2-yr rodent carcinogenicity bioassay. During a 26-wk study to assess the potential carcinogenicity of oxymetholone using p-cresidine as a positive control, glass/ polypropylene microchips (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 13 publications
1
42
1
1
Order By: Relevance
“…An advantage of transponder use is that they can be kept within tissues collected from the animals to keep tracking data from the original animal. In contrast to some long-term studies, 20,25,26 no tumours were detected in association with the transponders in 20-week-old C57BL/6J mice in the present study.…”
Section: Postmortem Analysiscontrasting
confidence: 99%
“…An advantage of transponder use is that they can be kept within tissues collected from the animals to keep tracking data from the original animal. In contrast to some long-term studies, 20,25,26 no tumours were detected in association with the transponders in 20-week-old C57BL/6J mice in the present study.…”
Section: Postmortem Analysiscontrasting
confidence: 99%
“…9,11 Once encapsulation is complete, a microchip transponder is expected to function safely; however, transponder-associated neoplasia has been described in laboratory mice, laboratory rats, pet dogs, an Egyptian fruit bat, a degu, and a feathertail glider. 3,4,10,[12][13][14][15] The majority of transponder-associated tumors have been mesenchymal in origin, and the mechanism of carcinogenicity is thought to be foreign body-induced tumorigenesis. 4 In this report, we describe the findings of tumors associated with implanted microchip transponders in 2 adult female Damaraland mole rats.…”
Section: Discussionmentioning
confidence: 99%
“…Five out of eight articles reported that 0.8 -4.1% of laboratory mice and rats developed malignant tumours around or adjacent to the implanted microchips. 22 In one of these eight studies, the investigators used a genetically modified line ( p53þ/2 mice) that was prone to develop cancer, and 10.2% of the mice developed tumours 5 and in several cases these tumours also metastasized. The tumours generally occurred in the second year of the studies, in middle aged or older animals.…”
Section: Microchip Transpondermentioning
confidence: 99%